Factors that influence specialist physician preferences for fee-for-service and salary-based payment models: A qualitative study. Issue 4 (April 2021) - Ogundeji, Yewande Kofoworola; Quinn, Amity; Lunney, Meaghan; Chong, Christy; Chew, Derek; Danso, George; Duggan, Shelly; Edwards, Alun; Hopkin, Gareth; Senior, Peter; Sumner, Glen; Williams, Jennifer; et al.
Highlights: Physicians' desire for flexibility or autonomy and their professional interests influence payment model preferences. Many early- to mid-career female physicians prefer payment models that offer flexibility and work-life balance. Attributes of alternative payment models might be more appealing to early-career physicians. Optimizing non-monetary attributes of alternative payment models may increase their voluntary selection by physicians. Abstract: Most physicians across the world are paid through fee-for-service. However, there is increased interest in alternative payment models such as salary, capitation, episode-based payment, pay-for-performance, and strategic blends of these models. Such models may be more aligned with broad health policy goals such as fiscal sustainability, delivery of high-quality care, and physician and patient well-being. Despite this, there is limited research on physicians' preferences for different models and a disproportionate focus on differences in income over other issues such as physician autonomy and purpose. Using qualitative interviews with 32 specialist physicians in Alberta, Canada, we examined factors that influence preferences for fee-for-service (FFS) and salary-based payment models. Our findings suggest that a series of factors relating to (1) physician characteristics, (2) payment model characteristics, and (3) professional interests influence preferences. Within these themes, flexibility, autonomy, and compatibility with academic roles were highlighted. To encourage physicians to select a specific payment model, the model must appeal to them in terms of income potential as well as non-monetary values. These findings can support constructive discussions about the merits of different payment models and can assist policy makers in considering the impact of payment reform.